Efeito de dois agentes dessensibilizantes sobre o grau de clareamento e sensibilidade da dentina, aplicados previamente ao clareamento de consultório – ensaio clínico controlado, randomizado, duplo-cego. - Godoy, Carlos Eduardo Misiak (2016)
This study evaluated the effectiveness of two desensitizing agents in preventing dentine sensitivity with no negative influence on the outcome of treatment with in-office bleaching. The bleaching was performed with 35% hydrogen peroxide, from second premolar to second premolar in the upper and lower arches of 20 patients, divided according to the desensitizing agent used prior to the bleaching procedure: Placebo (PL); Desensibilize KF (KFD) and Oxa-Gel (OG). The level of color saturation was assessed at the beginning of treatment and after one week of its completion by means of comparative method with the aid of a color scale. The degree of sensitivity (DS) was noted by the patients with the aid of a visual scale throughout the time that the bleaching agent remained in contact with the teeth (5, 10, 15, 20, 25 and 30 minutes) as well as 1, 24 and 48 hours after the end of application. The data of maximum pain reported and the degree of color saturation were evaluated using the Shapiro-Wilk test. The DS was assessed by Kruskal-Wallis and Dunn’s tests. The color was evaluated by ANOVA and Tukey's HSD. The results showed no significant differences in the degree of bleaching among the groups. DS was significantly more accentuated in the 48-hour period. The DS was significantly higher for the PL group and significantly lower for the OG one. The use of desensitizing agents reduced the DS without affecting the effectiveness of the bleaching treatment.